2019
DOI: 10.1515/jpem-2018-0403
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Greek version of the Quality of Life in Short Stature Youth (QoLISSY) questionnaire

Abstract: Background The Quality of Life in Short Stature Youth (QoLISSY) questionnaire is a condition-specific instrument for measuring the health-related quality of life (HRQoL) in short statured children/adolescents from patients’ and parents’ perspectives. The aim of this study was to investigate the psychometric properties of the Greek version of the QoLISSY questionnaire. Methods The original European QoLISSY scales were translated into Greek following the guidelines for linguistic validation and applied to 184 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Cronbach’s alpha varies between 0.65 and 0.95 [ 42 ]. The QoLISSY questionnaire is validated for ISS, IGHD [ 70 ], achondroplasia [ 71 ], and Small-for-Gestational Age [ 72 ] and is available in various languages, e.g., German, Englisch, Spain, Frech, Swedish [ 70 ], Italian [ 34 ], or Greek [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cronbach’s alpha varies between 0.65 and 0.95 [ 42 ]. The QoLISSY questionnaire is validated for ISS, IGHD [ 70 ], achondroplasia [ 71 ], and Small-for-Gestational Age [ 72 ] and is available in various languages, e.g., German, Englisch, Spain, Frech, Swedish [ 70 ], Italian [ 34 ], or Greek [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…For these languages we decided to perform the harmonization after the cognitive debriefing in the respective countries. Interestingly, in earlier studies [ 71 , 72 , 73 , 74 ], the cross-cultural harmonization process of HRQOL instruments in children of different languages has been performed in varying ways.…”
Section: Discussionmentioning
confidence: 99%
“…Bedside, Quitmann et al (2019) (43) were consistent with the current findings and concluded that improvements in quality of life of children were connected with a rise in height. Drosatou et al (2019) (44) suggested that taller children had higher quality of life. Furthermore, Silva et al (2018) (41) and Briceno al (2019) (45) found that children who treated and grew to normal height had a better quality of life than those who were not treated.…”
Section: Figure (3)mentioning
confidence: 99%